Features of brain electrical activity in adult patients with POLG-related disorders - P. A. Fedin; E. P. Nuzhnyi; T. Yu. Noskova; Yu. A. Seliverstov; S. A. Klyushnikov; T. D. Krylova; P. G. Tsygankova; E. Yu. Zakharova; S. N. Illarioshkin (Эпилепсия и пароксизмальные состояния, 2021)
Introduction. Epilepsy is a common feature of mitochondrial disorders, including those associated with mutations in the POLG gene. Nevertheless, brain electrical activity features of POLG-related disorders in adult patients have not been adequately studied. Objective. To study the features and characteristics of the electroencephalography (EEG) pattern in adult patients with POLG-related disorders. Material and methods. Eight patients were examined: 7 with SANDO (Sensory Ataxic Neuropathy, Dysarthria, Ophthalmoparesis) syndrome, and 1 with MEMSA (Myoclonic Epilepsy Myopathy Sensory Ataxia) syndrome; median age was 32.5 years. All patients underwent routine EEG monitoring using a 19-channel electroencephalograph according to the generally accepted method. Results. Epileptic seizures were found in 3 patients, for 2 of them – as the first manifestation of the disease. In 6 patients, theta waves predominated in the occipital regions. Of those 6 patients, in 5 bilateral synchronous bursts of theta and delta wave groups were identified being more prominent in the frontocentral regions; 4 patients had transient non-lateralized delta activity in the occipital and parieto-occipital brain regions. In all patients, opening eyes led to the depression of rhythms and burst suppression. After photostimulation, in 2 cases bilateral synchronous bursts of delta and theta wave groups were recorded predominantly in frontal lobes. In 3 patients during hyperventilation an increase in delta activity in the occipital lobes and bilateral synchronous bursts of delta wave groups were observed. Epileptiform activity was recorded in 2 cases. Conclusion. In adult patients with POLG-related disorders, regardless of the clinical manifestation, typical EEG features include generalized background slowing, theta and delta bursts in occipital lobes with their suppression by opening eyes.